Question and Answers Forum

All Questions      Topic List

Relation and Functions Questions

Previous in All Question      Next in All Question      

Previous in Relation and Functions      Next in Relation and Functions      

Question Number 132496 by mathmax by abdo last updated on 14/Feb/21

calculateA_n = Σ_(n=1) ^∞  (((−1)^n )/n^2 )cos(n) andB_n = Σ_(n=1) ^∞  (((−1)^n )/n^2 )cos(((nπ)/3))

calculateAn=n=1(1)nn2cos(n)andBn=n=1(1)nn2cos(nπ3)

Answered by mnjuly1970 last updated on 14/Feb/21

 by using dilogarithm function  or fourier series...  first  method..     f(x)=x         x∈[−π,π]      f is artificial periodic function  on [−π ,π]   f(x)≈(a_0 /2)+Σ_(n=1) (a_n cos(nx)+b_n sin(nx))  a_n =(1/π)∫_(−π) ^( π) f(x)cos(nx)dx=0  b_n =(1/π)∫_(−π) ^( π) f(x)sin(nx)dx        =(1/π)∫_(−π) ^( π) xsin(nx)dx=(2/π)∫_0 ^( π) xsin(nx)dx   =(2/π){[−(x/n)cos(nx)]_(0 ) ^π +(1/n)∫_0 ^( π) cos(nx)dx  2(−1)^(n+1) (1/n)  a_0 =(1/π)∫_(−π) ^( π) f(x)dx=0     x≈ Σ_(n=1) ^∞ ((2(−1)^(n+1) )/(n ))sin(nx)    ∫xdx≈2Σ_(n=1) ^∞ ∫ (((−1)^(n+1) )/(n ))sin(nx)dx  (x^2 /2)≈C+2Σ_(n=1) ^∞ (((−1)^n )/n^2 )cos(nx)    x=π⇒ (π^2 /2)≈C+2Σ_(n=1) (1/n^2 )      C=(π^2 /2)−(π^2 /3)=(π^2 /6)     (x^2 /2)=(π^2 /6)+2Σ_(n=1) ^∞ (((−1)^n )/n^2 )cos(nx)    x=1 ⇒(1/2)−(π^2 /6)=2Σ_(n=1) ^∞ (((−1)^n )/n^2 )        Σ_(n=1) ^∞ (((−1)^n )/n^2 )=(1/4)−(π^2 /(12))  ...

byusingdilogarithmfunctionorfourierseries...firstmethod..f(x)=xx[π,π]fisartificialperiodicfunctionon[π,π]f(x)a02+n=1(ancos(nx)+bnsin(nx))an=1πππf(x)cos(nx)dx=0bn=1πππf(x)sin(nx)dx=1πππxsin(nx)dx=2π0πxsin(nx)dx=2π{[xncos(nx)]0π+1n0πcos(nx)dx2(1)n+11na0=1πππf(x)dx=0xn=12(1)n+1nsin(nx)xdx2n=1(1)n+1nsin(nx)dxx22C+2n=1(1)nn2cos(nx)x=ππ22C+2n=11n2C=π22π23=π26x22=π26+2n=1(1)nn2cos(nx)x=112π26=2n=1(1)nn2n=1(1)nn2=14π212...

Commented by mathmax by abdo last updated on 14/Feb/21

thank you sir.

thankyousir.

Commented by mnjuly1970 last updated on 15/Feb/21

grateful...

grateful...

Answered by mnjuly1970 last updated on 14/Feb/21

   second method    Σ_(n=1) ^∞ (((−1)^n )/n^2 )(((e^(in) +e^(−in) )/2))  =(1/2)Σ_(n=1) ^∞ (((−e^i )^n )/n^2 ) +(1/2)Σ_(n=1) ^∞ (((−e^(−i) )^n )/n^2 )  =(1/2)(li_2 (−e^i )+li_2 (−(1/e^i )))  =_(((−π^2 )/6)−(1/2)ln^2 (z)) ^(li_2 (−z)+li_2 (−(1/z))) (1/2)(((−π^2 )/6)−(1/2)ln^2 (e^i ))   =((−π^2 )/(12))−(1/4)(i^2 )=((−π^2 )/(12))+(1/4)  ....

secondmethodn=1(1)nn2(ein+ein2)=12n=1(ei)nn2+12n=1(ei)nn2=12(li2(ei)+li2(1ei))=li2(z)+li2(1z)π2612ln2(z)12(π2612ln2(ei))=π21214(i2)=π212+14....

Answered by mathmax by abdo last updated on 14/Feb/21

let ϕ(x)=x  ,2π periodic odd ⇒ϕ(x)=Σ_(n=1) ^∞  a_n sin(nx)  a_n =(1/π)∫_(−π) ^π  x sin(nx)dx =(2/π)∫_0 ^π  xsin(nx)dx ⇒  (π/2)a_n =[−(x/n)cos(nx)]_0 ^π +∫_0 ^π (1/n)cos(nx)dx =−(π/n)(−1)^n  +(1/n^2 )[sin(nx)]_0 ^π   =−(π/n)(−1)^n  ⇒a_n =(2/π).(−(π/n))(−1)^n  =−(2/n)(−1)^n  ⇒  x=−2Σ_(n=1) ^∞   (((−1)^n )/n)sin(nx)  ⇒(x^2 /2) =2Σ_(n=1) ^∞  (((−1)^n )/n^2 )cos(nx) +C  x=0 ⇒0 =2 Σ_(n=1) ^∞  (((−1)^n )/n^2 ) +c  =2.(2^(1−2) −1)ξ(2)+C  =2(−(1/2))(π^2 /6) +C =−(π^2 /6) +C ⇒C =(π^2 /6) ⇒  (x^2 /2) =2Σ_(n=1) ^∞  (((−1)^n )/n^2 )cos(nx)+(π^2 /6) ⇒2Σ(....)=(x^2 /2)−(π^2 /6) ⇒  Σ_(n=1) ^∞  (((−1)^n )/n^2 )cos(nx) =(x^2 /4)−(π^2 /(12))  x=1 ⇒Σ_(n=1) ^∞  (((−1)^n )/n^2 )cos(n) =(1/4)−(π^2 /(12))  x=(π/3) ⇒Σ_(n=1) ^∞  (((−1)^n )/n^2 )cos(n(π/3))=(π^2 /(36))−(π^2 /(12)) =(π^2 /(36))−((3π^2 )/(36)) =−(π^2 /(18))

letφ(x)=x,2πperiodicoddφ(x)=n=1ansin(nx)an=1πππxsin(nx)dx=2π0πxsin(nx)dxπ2an=[xncos(nx)]0π+0π1ncos(nx)dx=πn(1)n+1n2[sin(nx)]0π=πn(1)nan=2π.(πn)(1)n=2n(1)nx=2n=1(1)nnsin(nx)x22=2n=1(1)nn2cos(nx)+Cx=00=2n=1(1)nn2+c=2.(2121)ξ(2)+C=2(12)π26+C=π26+CC=π26x22=2n=1(1)nn2cos(nx)+π262Σ(....)=x22π26n=1(1)nn2cos(nx)=x24π212x=1n=1(1)nn2cos(n)=14π212x=π3n=1(1)nn2cos(nπ3)=π236π212=π2363π236=π218

Commented by mnjuly1970 last updated on 15/Feb/21

very nice sir max..

verynicesirmax..

Terms of Service

Privacy Policy

Contact: info@tinkutara.com